The Effects of Climate on Microalgae Growth in Arctic Wastewater Stabilization Ponds - Maassarani, Rami (2015)
Thesis (Master, Civil Engineering) -- Queen's University, 2015-05-29 08:50:15.104 The research presented in this thesis consists of work conducted in two studies designed to evaluate temperature effects on microalgal growth in Arctic wastewater stabilization ponds (WSPs). These systems are commonly used to treat municipal wastewater in small arctic communities, however, summer temperatures that rarely exceed 20oC could potentially limit microalgal growth. The presence of microalgae in these systems has been suggested to enhance wastewater treatment efficiency due to the synergistic relationship between microalgae and heterotrophic bacteria, supporting the need to develop a better understanding regarding the effects of climate and summer temperatures on microalgal growth for areas north of the 54th parallel. The first study investigated the effects of temperature on the growth of the microalgal strain Chlorella vulgaris. Experimental data were subsequently compared against three models developed to predict algae growth as a function of temperature. Growth rates were evaluated for a range of 1-23oC and experimental results showed a strong correlation between maximum microalgal growth rates and temperature, where maximum microalgal growth rates were found to be at their lowest at 1oC and peaked at 23oC. The experimental data were then compared to the maximum growth values predicted by three mathematical models: the Eppley Curve, an Arrhenius Relationship and the Peeters & Eilers model. The latter was deemed to be the most suitable model for microalgal growth rates in arctic WSPs, as it predicted the maximum growth rates of C. vulgaris reliably for the temperature range of 1-23oC. The second study involved the modification of an existing numerical model which was developed to simulate biochemical processes in WSPs. The Peeters & Eilers growth equation was incorporated into this numerical model, along with historical weather data from Pond Inlet, NU in order to characterize the effects of arctic ...